NAFAKADAN FERAGAT - (:unkn) unknown (My University, 2016)
Nafaka, karı veya kocanın ayrılık veya boşanmadan sonra veya bu davalar sırasında, eşi ve çocukları için maddi anlamda katkı sağlaması anlamına gelir. Nafaka karı veya koca için olabileceği gibi, çocuklar için de söz konusu olabilir. Bu makalede, Türk Medeni Kanunu'nda nafaka türleri, Medeni Usul Hukukunda feragat kavramı ve son olarak nafaka talebinden feragat talebi incelenecektir.

Alimony is meaning that a husband's or wife's provision about financial support for a spouse or their children after separation or divorce or process of these lawsuit. Alimony is a matter for not only husband or wife but also children. In this article, we focus on types of alimony in Turkish Civil Code, the concept of waiver in Civil Procedural Law, and finally, waiver a claim for alimony.
Waive From Maintenance Payment
Keywords: Hukuk